Pressure Ulcer Monitoring Platform-A Prospective, Human Subject Clinical Study to Validate Patient Repositioning Monitoring Device to Prevent Pressure Ulcers - Minteer, Danielle M; Simon, Patsy; Taylor, Donald P; Jia, Wenyan; Li, Yuecheng; Sun, Mingui; Rubin, J Peter (Advances in wound care (New Rochelle, N.Y.), 2020)
The objective of this prospective clinical study was to validate two prototype pressure ulcer monitoring platform (PUMP) devices, (PUMP1 and PUMP2), to promote optimal bed repositioning of hospitalized patients to prevent pressure ulcers (PUs). PUMP1 was a wearable electronic device attached to the patient gown with no skin contact. PUMP2 was a set of four identical electronic devices placed under the patient's bed wheels. A video camera recorded events in the patient room while measurements from the PUMP devices were correlated with true patient repositioning activity. The performance of these PUMP devices developed by our research team were evaluated and compared by both clinicians and engineers. Ten mobility-restricted patients were enrolled into the study. Repositioning movement was recorded by both PUMP devices for 10 ± 2 h and corroborated with video capture. One hundred thirty-seven movements in total were detected by both PUMP1 and PUMP2 over 105 h of capture. Two false positives were detected by the sensors and 11 movements were missed by the sensors. PUMP1 and PUMP2 never conflicted in data collection. The presented study evaluated two different sensors' abilities to capture accurate patient repositioning to eventually prevent PU formation. Importantly, detection of patient motion was completed without contact to patient skin. The clinical study demonstrated successful capture of patient repositioning movement by both PUMP1 and PUMP2 devices with 85% reliability, 2 false positives, and 11 missed movements. In future studies, the PUMP devices will be combined with a SMS-based mobile phone alert system to improve caregiver repositioning behavior.